Arthroscopic Resection of Distal Clavicular Osteochondroma: A Case Report. Issue 2 (April 2021) - Lopez-Ovenza, Juan M.; San Roque, Mariamar; Olvi, Liliana G.
Abstract : Case: A 23-year-old boy presented with a 3-month history of right shoulder pain. Radiographs and computed tomography showed an exostosis on the inferior aspect of the distal clavicle. It was osteotomized and removed by arthroscopy. The histological examination confirmed the diagnosis of osteochondroma. The patient was found asymptomatic with full range of motion in the last clinical control at 1 year of follow-up. Conclusion: This case report shows an arthroscopic resection of distal clavicular osteochondroma achieving complete resection of the tumor with an excellent clinical outcome. The technique offers a direct view of the inferior aspect of the clavicle and preserves the acromioclavicular joint.